2015
DOI: 10.5339/gcsp.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in rheumatic valvular disease: Surgical strategies for mitral valve preservation

Abstract: In developing countries, rheumatic fever and carditis still constitutes a major public health problem. Patients have special characteristics that differ from those with rheumatic mitral valve disease we still see in developed countries. They are usually young, poor, uneducated, and have low compliance to prophylaxis / therapy. In addition, they usually have great difficulty in accessing medical care. In these situations, the rate of complications associated to valve replacement is significantly increased. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…When possible, it has been demonstrated that vavuloplasty is the best option; Antunes (27) in 1990 has reported a comparative study between valve reconstruction and rheumatic mitral valve disease; he analysed three groups: patients with mitral vavuloplasty (n=241); MRV by mechanical prosthesis (n=386) and bioprosthesis (n=289). Early mortality was significantly better after plasty 3% than mechanical valve replacement 7.8% or bioprothesis 6.6%; actuarial global survival and survival free from valve related complication were far better for vavuloplasty than replacement 90%±4% and 70%±6% for vavuloplasty versus 76%±3% and 71%±5% for mechanical valve replacement and 62%±7% and 30%±7% for bioprosthesis valve replacement; in another study the same author (28) has demonstrated that repair of mitral regurgitation can be performed in most cases with a repair rate of nearly 81% with excellent immediate, medium term results and in a well-controlled situation a survival of 89% and a survival free from reoperation of 85% at 15 years. Similar results have been shown by Kumar et al (29) in India with a 90% survival at the same follow-up duration.…”
Section: Rheumatic Heart Diseasesmentioning
confidence: 87%
“…When possible, it has been demonstrated that vavuloplasty is the best option; Antunes (27) in 1990 has reported a comparative study between valve reconstruction and rheumatic mitral valve disease; he analysed three groups: patients with mitral vavuloplasty (n=241); MRV by mechanical prosthesis (n=386) and bioprosthesis (n=289). Early mortality was significantly better after plasty 3% than mechanical valve replacement 7.8% or bioprothesis 6.6%; actuarial global survival and survival free from valve related complication were far better for vavuloplasty than replacement 90%±4% and 70%±6% for vavuloplasty versus 76%±3% and 71%±5% for mechanical valve replacement and 62%±7% and 30%±7% for bioprosthesis valve replacement; in another study the same author (28) has demonstrated that repair of mitral regurgitation can be performed in most cases with a repair rate of nearly 81% with excellent immediate, medium term results and in a well-controlled situation a survival of 89% and a survival free from reoperation of 85% at 15 years. Similar results have been shown by Kumar et al (29) in India with a 90% survival at the same follow-up duration.…”
Section: Rheumatic Heart Diseasesmentioning
confidence: 87%
“…Major advances in medical and surgical treatments for RHD have led to increased survival, which may also contribute to an increased prevalence of RHD 3,6 . Although valve replacement provides good early results, the patients usually have difficulty in accessing medical care, with a high rate of prosthesis-related complications 16 . Unfortunately, many patients present with valve dysfunction too advanced to benefit from cardiac surgery, and the mortality in these patients remains high 15,17,18 .…”
Section: Introduction: Overview Of Rheumatic Heart Diseasementioning
confidence: 99%
“…Hence, when we formulated the PGSRMVL, we gave those pathological lesions related to sub-valvular apparatus and calcification a higher weight value, based on special pathological characteristics. Because of the particular pathological characteristics shown among our cases, the surgical techniques used in our centre were also different from those of other centres (4,6,13,(22)(23)(24). The majority of the patients were treated via commissurotomy (90.5%) and thinning (70.39%).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are many discrepancies between the pathological characteristics described in those studies and those described for Chinese patients. For example, the preoperative pathology was regurgitation in most cases, and the ratio of stenosis and mixed lesion was low (3,6,7). The proportion of women was low (3), and the majority of patients were young and middle-aged (8,9).…”
mentioning
confidence: 99%